Evaluation of Environmental Fee Management Information System Using User Acceptance Test - Indra Gunawan; Khairina Eka Setyaputri (Brilliance: Research of Artificial Intelligence, 2026)
The management of environmental fees in residential areas requires an information system that is capable of supporting accurate transaction recording and transparent information delivery. Previously, Sunderland Jambi Housing Estate managed environmental fee administration using a manual system, which potentially caused recording errors, data inconsistency, and delays in information dissemination to residents. These limitations reduced the effectiveness and transparency of financial management processes. This study aims to evaluate the implementation of a web-based Environmental Fee Management Information System (SIM-IPL) at Sunderland Jambi Housing Estate. The research method applied is descriptive with a case study approach. Data were collected through observation, interviews, and questionnaires distributed to 20 active system users. System testing was conducted using Black Box Testing and User Acceptance Test (UAT) methods. The results of Black Box Testing indicate that all main system functionalities, including user authentication, transaction processing, data management, and financial reporting, operate according to the specified functional requirements. Furthermore, the UAT results show an overall average score of 4.88 or 97.6%, which is categorized as excellent. These results demonstrate that SIM-IPL is easy to use, improves financial information transparency, and provides a high level of user satisfaction. Therefore, it can be concluded that the web-based SIM-IPL is feasible and effective for supporting environmental fee management at Sunderland Jambi Housing Estate and can serve as a reference for similar residential financial management systems.